Penggunaan Aplikasi ACMT dan AP2T Dalam Proses Pembuatan Rekening Pelanggan di PT. PLN (Persero) UP3 Bandung - Arzumira Tsara Salsabilla; Mokhamad Hendayun; Chandra Hendriyani (Jurnal Sekretaris dan Administrasi Bisnis, 2022)
Some sectors of the country industry including PT PLN (Persero) are one of the state's revenue support in the field of electricity. In this era of digitization PT PLN (Persero) has implemented electronic Data processing system (PDE) including in the use of centralized record Meter application (ACMT) and centralized customer service Application (AP2T) for the creation of customer accounts to be more accurate and timely. The research methodology used is qualitative with a descriptive approach. The data collection techniques undertaken are observations, interviews and literature from the journal. The results showed that the use of electronic data processing system in PT PLN (Persero) is able to make process of customer account creation become more effective and efficient so that customer's account can be sent to PT PLN partner with Payment Point Online Bank (PPOB) in a timely manner.